2017
DOI: 10.5935/1518-0557.20170022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro fertilization outcomes in ICSI cycles after human sperm preparation by density gradient centrifugation and direct micro swim-up without centrifugation

Abstract: ObjectiveThe aim of this study was to evaluate the efficacy of a non-expensive, easy and fast technique (direct micro swim-up) for sperm preparation in intracytoplasmic sperm injection (ICSI) treatments without the use of centrifuge.MethodsWe carried out a multicentric study in which a total of 140 ICSI-cycles were included. Sibling oocytes were divided into two groups according to semen preparation procedures: group A, discontinuous gradients (DG) (oocytes n=668), and group B, direct micro swim-up (MSU) (oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
16
1
1
Order By: Relevance
“…We reported herein that DSU technique did not show any significant difference in all ART outcomes as compared to the DGC-SU technique. However, Our results were inconsistent with the findings of Palini and colleagues in ICSI cycles [20]. Their results stated that blastulation rates per D3 embryos or per fertilized oocyte and pregnancy rates in DSU group were significant higher when compared to DGC-SU group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We reported herein that DSU technique did not show any significant difference in all ART outcomes as compared to the DGC-SU technique. However, Our results were inconsistent with the findings of Palini and colleagues in ICSI cycles [20]. Their results stated that blastulation rates per D3 embryos or per fertilized oocyte and pregnancy rates in DSU group were significant higher when compared to DGC-SU group.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding suggests that density-gradient centrifugation should be avoided during sperm preparation [19]. In addition, the DGC-SU technique requires operators to transfer sperm sample among several tubes, thereby increasing the potential risk of mismatches [5,[20][21]. These limitations, in concert, suggested that the DGC-SU was not optimal technique for sperm preparation for IVF and ICSI treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time saving of the investigated novel technique which is much faster than the classical sperm preparation procedure, is relevant particularly in avoiding the centrifugation steps using density gradients usually requiring up to 20 min, as well as subsequent centrifugations with the culture media to wash the pellet and remove any gradient compound that means more than 10 min, and finally the swim-up from pellet which takes normally between 40 and 50 min [ 26 , 27 ]. On the contrary, the novel procedure here reported, requires a total of 10 min to prepare the sperm, with a time saving of about 50 min compared with the direct swim-up procedure and further 75–80 min when including the density gradient step in the preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques isolate a population of highly motile, morphologically normal sperm and result in similar ART outcomes. 75 However, the live birth rate following ICSI remains frustratingly static at 25-30% per (fresh) treatment cycle. 76 Various advanced sperm selection techniques have been proposed in the hope of improving this.…”
Section: New Developments In Sperm Selection In Artmentioning
confidence: 99%